Surgical contraception. - Palma Guevara, Roberto (2015)
This is a research of 620 women, in whom the National Institute Perinatal and Maternal (Hospital Maternidad de Lima) between December 1990 than December 1992 did a voluntary surgeesl contraception in ambulatory system. This proceding has been did in post-partum, post-abortion uncomplicated and interval; with the actual legal norms and the standard of judgement of reproductive risks. The procedery is with local suestlezia and -redation; we did with minilap a Bilateral Pomeroy, We observed the how coat and resources and without compleations. Poat partum. pomeroy was in 74.7%; internal pomeroy was a 24.1% and uncomplicated post abortion pomeroy was in 1.2%. In the case of pomeroy post-partum, (the voluntary surgical contraception, use) the 53.6% was did in the 20 day of puerperium; the 29.5% was did in the 30 day. The % of our patients had high school level. Maybe with a better degree of educational lavel is a greater responsability in has reproductive health. The 38.3% of our patients had more of 4 children. Only 5 cases, the use was did in women with 1 child because for neuro psiguiative reasons. We concluded that the voluntary surguse contraception with mink lap and local anesthesia and sedation is a good alternative for women that has finished her reproductive cicle; with a how cost for the services of the Ministery of Health.